Psychometric characteristics of the Ukrainian-language versions of the scales of unreality of loss, maladaptive cognitions, and anxious-depressive avoidance in a sample of individuals who experienced the loss of a loved one in wartime - Leshchuk Ірина; But Тетяна; Zelenko Єлизавета; Frankova Ірина (Psychosomatic Medicine and General Practice, 2025)
Background. The full-scale war in Ukraine has caused mass casualties and widespread psychological trauma, placing many individuals at heightened risk of complicated grief and, in clinical terms, prolonged grief disorder (PGD). The cognitive-behavioral model of complicated grief emphasizes the role of the experience of unreality of loss, maladaptive cognitions, and avoidance in maintaining grief symptoms. Despite this, no validated Ukrainian-language tools exist to measure these processes. Aim. The aim of the study is to evaluate the psychometric properties of the Ukrainian-language versions of the Experience of Unreality Scale (EUS), the Grief Cognitions Questionnaire – 12-item short version (GCQ-12), and the Depressive and Anxious Avoidance in Prolonged Grief Questionnaire – 5-item short version (DAAPGQ-5) in a sample of individuals experiencing bereavement in the context of an ongoing war. Methods. A cross-sectional online study was conducted with 194 adult Ukrainian-speaking participants. All instruments were translated using a forward-backward procedure. Analyses included internal consistency (Cronbach’s α, McDonald’s ω), confirmatory factor analysis (CFA), convergent validity (Spearman correlations with TGI-SR-ICD-11, PCL-5, PHQ-4, WRSS, and SCES+), and known-groups validity. Results. All three instruments demonstrated acceptable or high internal consistency (EUS: α = 0.941; GCQ-12: α = 0.916; DAAPGQ-5: α = 0.829 for depressive and 0.698 for anxious avoidance). CFA confirmed a one-factor model for the EUS (after allowing residual covariance) and a two-factor structure for the DAAPGQ-5; for the GCQ-12, the one-factor model showed inadequate fit without accounting for correlated residuals between conceptually similar items. The GCQ-12 and DAAPGQ-5 demonstrated expected associations in convergent validity testing, whereas the EUS did not. Discussion. Overall, the results support the use of the Ukrainian-language GCQ-12 and DAAPGQ-5 for studying grief mechanisms in wartime. The EUS demonstrated strong internal consistency and confirmed unidimensionality; its lack of expected correlations with other measures may reflect the relative autonomy of loss unreality as a phenomenon under conditions of mass wartime trauma. The GCQ-12 showed some heterogeneity in its internal structure, suggesting that interpretation should go beyond a single total score. The findings are consistent with the cognitive-behavioral model of complicated grief, while also highlighting the influence of the wartime context on the specific features of loss experience. Conclusions. The Ukrainian-language versions of the EUS, GCQ-12, and DAAPGQ-5 showed adequate psychometric properties and can be recommended for use in both clinical practice and research to assess grief mechanisms in wartime populations. Key words: prolonged grief disorder; complicated grief; psychometric validation; unreality of loss; maladaptive cognitions; anxious and depressive avoidance; cognitive-behavioral model of grief.